Susceptibility of Drosophila suzukii larvae to the combined administration of the entomopathogens Bacillus thuringiensis and Steinernema carpocapsae - Maristella Mastore (Nature Portfolio, 2021)
Abstract Non-native pests are often responsible for serious crop damage. Since Drosophila suzukii has invaded North America and Europe, the global production of soft, thin-skinned fruits has suffered severe losses. The control of this dipteran by pesticides, although commonly used, is not recommended because of the negative impact on the environment and human health. A possible alternative is the use of bio-insecticides, including Bacillus thuringiensis and entomopathogenic nematodes, such as Steinernema carpocapsae. These biological control agents have a fair effectiveness when used individually on D. suzukii, but both have limits related to different environmental, methodological, and physiological factors. In this work, we tested various concentrations of B. thuringiensis and S. carpocapsae to evaluate their efficacy on D. suzukii larvae, when administered individually or in combination by using agar traps. In the combined trials, we added the nematodes after 16 h or concurrently to the bacteria, and assessed larvae lethality from 16 to 48 h. The assays demonstrated a higher efficacy of the combined administration, both time-shifted and concurrent; the obtained data also showed a relevant decrease of the time needed to kill the larvae. Particularly, the maximum mortality rate, corresponding to 79% already at 16 h, was observed with the highest concentrations (0.564 µg/mL of B. thuringiensis and 8 × 102 IJs of S. carpocapsae) in the concurrent trials. This study, conducted by laboratory tests under controlled conditions, is a good starting point to develop a further application step through field studies for the control of D. suzukii.